2021
DOI: 10.1088/2040-8986/ac1fc4
|View full text |Cite
|
Sign up to set email alerts
|

Vortex surface plasmon polaritons on a cylindrical waveguide: generation, propagation, and diffraction

Abstract: In this paper, we experimentally demonstrated excitation of terahertz vortex surface plasmon polaritons by end-fire coupling of radially-polarized annular beams with orbital angular momentum (the wavelength was 141 µm, and the topological charges were ±3 and ±9) to a 70 mm long, simply connected axis-symmetric transmission line and their propagation to the end of the line and diffraction into a free wave possessing the same topological charge as the input beam. The diameter of the line exceeded greatly the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
2
Order By: Relevance
“…It is important to note that information about the intensity distribution in the crosssection of perfect beams is crucial for planning and conducting experiments on the excitation of vortex plasmons on cylindrical samples [64] (see Section 1). Plasmons were excited on a brass cylinder coated with a ZnS dielectric layer using the end-fire coupling technique.…”
Section: Perfect Beams Formed With Binary and Holographic Axiconsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that information about the intensity distribution in the crosssection of perfect beams is crucial for planning and conducting experiments on the excitation of vortex plasmons on cylindrical samples [64] (see Section 1). Plasmons were excited on a brass cylinder coated with a ZnS dielectric layer using the end-fire coupling technique.…”
Section: Perfect Beams Formed With Binary and Holographic Axiconsmentioning
confidence: 99%
“…In [62,63], it was shown that the diffraction of a Bessel beam by a periodic two-dimensional grating in the Talbot planes results in the formation of periodic gratings of annular microbeams, which can be regarded as analogs of perfect beams. A very interesting application was demonstrated in [64], where beams with orbital angular momentum were first used to excite vortex surface plasmon polaritons propagating along a cylindrical conductor for a distance of up to 150 mm. The Bessel beam was first transformed by means of a lens into the so-called "perfect beam" of an annular configuration [65][66][67][68] (see detailed description in Section 3.3), which when diffracting at the front edge of the cylinder [69][70][71], excited vortex plasmons around the perimeter.…”
Section: Introductionmentioning
confidence: 99%
“…Интегральная интенсивность излучения (нормированная на максимальное значение) в пределах кадров, показанных на рис. 2, для бинарного (BA) и голографического (HA) аксиконовСовершенные пучки, сформированные описанными выше аксиконами, использовались для генерации вихревых поверхностных плазмон-поляритонов (ВППП) терагерцового диапазона на осесимметричных проводящих линиях[28], которая показала возможность реализации плазмонных мультиплексных передающих линий, предложенных в[29]. Плазмоны, несущие орбитальный угловой момент с |  |  9, возбуждались методом дифракции (end-fire coupling technique) совершенных пучков, показанных на рис.…”
unclassified
“…3ж), оказалась благоприятным фактором для эксперимента. Она позволила возбудить на краю цилиндра 18 независимых параллельно движущихся поверхностных плазмон-поляритонов, что дало возможность продемонстрировать (детали см [28]…”
unclassified